Implementing Genomic Testing for Lung Cancer Into Routine Clinical Practice – The Welsh Experience. Issue 11 (November 2022) - Cox, S.; Powell, C.; Morgan, S.
Abstract: Aims: Over the last decade there has been a rapid expansion of clinically actionable driver mutations in non-small cell lung cancer (NSCLC), with an unprecedented number of corresponding targeted therapies approved and funded for use in the clinic. Here we summarise the approach taken in Wales to embed a NSCLC biomarker testing pathway within the National Optimal Pathway for Lung Cancer. Materials and methods: The Welsh Thoracic Oncology Group established a working group tasked with progressing the standardisation of genomic testing. In July 2021, the 10 lung cancer multidisciplinary teams (MDTs) were invited to take part in a national survey of current biomarker testing practices and a retrospective audit of the next generation sequencing (NGS) pathway in Wales was conducted. Results: Seventy per cent of MDTs completed the survey, which confirmed variability in the approach to testing with respect to timing of requests, patient selection and testing technologies used. Only 43% reported having pathology-initiated reflex testing, but 87% had adopted DNA and RNA NGS testing as their standard-of-care genomic testing strategy. Data from 53 patients with stage III–IV NSCLC with genomic testing requested between October 2020 and May 2021 were analysed in the NGS pathway audit. Forty (75.5%) patients had both DNA and RNA NGS requested, with a median turnaround time from biopsy to results of 26 days (range 19–37 days) and 25 days (range 16–38 days), respectively. The geographical location of MDT did not influence turnaround times and MDTs with reflex testing had shorter biopsy-to-result times. DNA NGS testing was successful in 51 (96.2%) patients; in those who had RNA NGS, testing was successful in 30 (75%) patients. Conclusion: Significant progress has been made within Wales to implement a national biomarker testing pathway, with reflex testing becoming standard of care. However, challenges remain in optimising the quantity and quality of tissue available for testing, together with a need to reduce turnaround times. This will need to be addressed to ensure all eligible patients are tested at the right time in the diagnostic pathway to facilitate optimal treatment strategies and ultimately improve outcomes.